(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Experiments were conducted to find out different soil fungi from wheat cultivated area during 15 April to 10 May, 2013-2014. The obtained soil fungi from wheat cultivated area were Aspergillus spp., Penicillum spp., Geotrichum spp., Gloesporium spp., Fusarium spp., Mycelia sterilia, Arthrobotrys spp., Cladosporium herbarum in district Allahabad, Various soil fungi from wheat cultivated area from Mirzapur district were which Aspergillus spp., Penicillum spp., Rizoctinia spp., Fusarium spp., Mucor spp. and In Varanasi district, various soil fungi were obtained also from wheat cultivated area which are Aspergillus spp., Penicillum spp., Rizoctinia spp., Fusarium spp., Mucor spp., Alternaria spp., Helminthosporium oryzae, and Humicola grisea. Aspergillus spp. and Penicillum spp. was common fungi presented in three different districts Allahabad, Mirzapur and Varanasi, of Uttar Pradesh. Bangladesh J. Agril. Res. 43(1): 149-157, March 2018